2005
DOI: 10.1104/pp.104.053991
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidioschyzon merolae Genome. A Tool for Facilitating Comparable Studies on Organelle Biogenesis in Photosynthetic Eukaryotes  

Abstract: The ultrasmall unicellular red alga Cyanidioschyzon merolae lives in the extreme environment of acidic hot springs and is thought to retain primitive features of cellular and genome organization. We determined the 16.5-Mb nuclear genome sequence of C. merolae 10D as the first complete algal genome. BLASTs and annotation results showed that C. merolae has a mixed gene repertoire of plants and animals, also implying a relationship with prokaryotes, although its photosynthetic components were comparable to other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
79
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 67 publications
1
79
0
Order By: Relevance
“…Unicellular red algae appear to a have single, large and highly convoluted mitochondrion as first demonstrated in the three dimensional reconstruction of Rhodella maculata L. Evans (Broadwater and Scott 1986) and later confirmed, based on fluorescence microscopy of Cyanidium caldarium (Tilden) Geitler and Galdieria sulphuraria (Galdieri) Merola (Suzuki et al 1994). These unicellular red algae have proven to be useful model systems for studies of mitochondrial division (e.g., Kuroiwa 1998Kuroiwa , 2000Miyagishima et al 2001;Misumi et al 2005). Studies of multicellular red algae showed that many mitochondria were present in these algae (Russell et al 1993;Garbary and McDonald 1998;Garbary and Pei 2000a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Unicellular red algae appear to a have single, large and highly convoluted mitochondrion as first demonstrated in the three dimensional reconstruction of Rhodella maculata L. Evans (Broadwater and Scott 1986) and later confirmed, based on fluorescence microscopy of Cyanidium caldarium (Tilden) Geitler and Galdieria sulphuraria (Galdieri) Merola (Suzuki et al 1994). These unicellular red algae have proven to be useful model systems for studies of mitochondrial division (e.g., Kuroiwa 1998Kuroiwa , 2000Miyagishima et al 2001;Misumi et al 2005). Studies of multicellular red algae showed that many mitochondria were present in these algae (Russell et al 1993;Garbary and McDonald 1998;Garbary and Pei 2000a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Cyanidioschyzon merolae is a unicellular red alga living in sulfate-rich, acidic hot springs. It has been used to elucidate aspects of eukaryotic cell biology such as the evolutionary origins and function of organelles, and the effects of compact genomes, and it was the first alga for which the complete genome sequence was produced and annotated (Matsuzaki et al, 2004;Misumi et al, 2005;Nozaki et al, 2007). Because the cell contains a minimal set of organelles, one nucleus, one mitochondrion, one chloroplast and one peroxisome, C. merolae is an ideal model organism, particularly for studying inter-organelle interactions.…”
mentioning
confidence: 99%
“…It is considered to be one of the most primitive algal species , Matsuzaki et al 2004, Nozaki et al 2007. The alga has a simple cellular structure, with each cell having one nucleus, one mitochondrion, and one plastid plus other organelles, such as a Golgi body, endoplasmic reticulum, a microbody and a few lysosomes (Kuroiwa et al 1994, Misumi et al 2005). The nucleus, mitochondrion and plastid genomes of this species have been completely sequenced, representing the first algal genome (Matsuzaki et al 2004, Nozaki et al 2007, Ohta et al 2003.…”
mentioning
confidence: 99%